Vibrational signature of the graphene nanoribbon edge structure from high-resolution electron energy-loss spectroscopy. Issue 38 (30th September 2020) - Cavani, Nicola; De Corato, Marzio; Ruini, Alice; Prezzi, Deborah; Molinari, Elisa; Lodi Rizzini, Alberto; Rosi, Agnese; Biagi, Roberto; Corradini, Valdis; Wang, Xiao-Ye; Feng, Xinliang; Narita, Akimitsu; et al.
Abstract : A combined experimental and theoretical investigation of the vibrational signatures of on-surface synthesized graphene nanoribbons demonstrates the potentiality of HREELS in disclosing the details of their edge structure. Abstract : Bottom-up approaches exploiting on-surface synthesis reactions allow atomic-scale precision in the fabrication of graphene nanoribbons (GNRs); this is essential for their technological applications since their unique electronic and optical properties are largely controlled by the specific edge structure. By means of a combined experimental-theoretical investigation of some prototype GNRs, we show here that high-resolution electron energy-loss spectroscopy (HREELS) can be successfully employed to fingerprint the details of the GNR edge structure. In particular, we demonstrate how the features of HREEL vibrational spectra – mainly dictated by edge CH out-of-plane modes – are unambiguously related to the GNR edge structure. Moreover, we single out those modes which are localized at the GNR termini and show how their relative intensity can be related to the average GNR length.